Variations in Nuclear Number and Size in Vegetative Hyphae of the Edible Mushroom Lentinula edodes - Gao, Qi; Yan, Dong; Wang, Dan; Gao, Shanshan; Zhao, Shuang; Wang, Shouxian; Liu, Yu (Frontiers in Microbiology, 2019)
In basidiomycete fungi, the number of nuclei and their ploidy level per nucleus can vary tremendously among species; however, within species, nuclear number and ploidy levels are traditionally considered fixed in their vegetative hyphae. In the edible mushroom Lentinula edodes, the hyphae are classified as either monokaryotic or dikaryotic, with each monokaryotic hyphal cell containing one haploid nucleus, and each dikaryotic hyphal cell containing two haploid nuclei. The dikaryotic hyphae are the results of mating between two genetically distinct monokaryons with different mating types. In this study, we examined the nuclear number and size (a potential correlate to ploidy) of L. edodes mycelia throughout its vegetative growth. We found that the number of nuclei within individual hyphal cells varied widely from non-nucleated to uninucleated, dinucleated, and multinucleated. Additionally, different nuclei within the same cell appeared very different in size, with a maximum nucleus cross-sectional area of 4.94 μm2 and the minimum nucleus cross-sectional area at only 0.37 μm2. Moreover, as culture time increased, more cells appeared to be devoid of any nuclei, with transmission electron microscopy and terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) assays of late-stage cultures showing autophagosomes fusing and dissolving the nuclei and resulting in a large number of TUNEL-positive DNA fragments in non-nucleated cells. These results indicated that non-nucleated cells were likely caused by autophagy and apoptosis-like activities within aging L. edodes hyphae.